Analisis Pengelolaan Dana Ziswaf Berdasarkanpsak 109 (Studi pada Masjid Nuruushaalihin, Desa Bacu Kecamatan Barebbo Kabupaten Bone) - Yunita, Vira; Syaputra, Muh.Fadli; Hasbi, Hartas (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research provides the management of ZISWAF (Zakat, Infaq, Alms and Waqf) funds in mosques from the perspective of PSAK 109. With a qualitative approach, this research identifies the gap between fund management practices in mosques and applicable sharia accounting standards. Mosques provide simple recording manuals and do not refer to the principles of transparency and accountability regulated in PSAK 109. The research results show that a lack of sharia accounting literacy is the main obstacle in implementing these standards. Therefore, it is necessary to increase the capacity of mosque managers through training and technical assistance to improve the quality of management of ZISWAF funds and build public trust in religious institutions.